Cerebrospinal Fluid Early Fungicidal Activity as a Surrogate Endpoint for Cryptococcal Meningitis Survival in Clinical Trials. (8th January 2020) - Pullen, Matthew F; Hullsiek, Katherine Huppler; Rhein, Joshua; Musubire, Abdu K; Tugume, Lillian; Nuwagira, Edwin; Abassi, Mahsa; Ssebambulidde, Kenneth; Mpoza, Edward; Kiggundu, Ruben; Akampurira, Andrew; Nabeta, Henry W; et al.
Abstract: Background: In cryptococcal meningitis phase 2 clinical trials, early fungicidal activity (EFA) of Cryptococcus clearance from cerebrospinal fluid (CSF) is used as a surrogate endpoint for all-cause mortality. The Food and Drug Administration allows for using surrogate endpoints for accelerated regulatory approval, but EFA as a surrogate endpoint requires further validation. We examined the relationship between rate of CSF Cryptococcus clearance (EFA) and mortality through 18 weeks. Methods: We pooled individual-level CSF data from 3 sequential cryptococcal meningitis clinical trials conducted during 2010–2017. All 738 subjects received amphotericin + fluconazole induction therapy and had serial quantitative CSF cultures. The log10 -transformed colony-forming units (CFUs) per mL CSF were analyzed by general linear regression versus day of culture over the first 10 days. Results: Mortality through 18 weeks was 37% for EFA > = 0.60 (n = 170), 36% for 0.40–0.59 (n = 182), 39% for 0.30–0.39 (n = 112), 35% for 0.20–0.29 (n = 87), and 50% for those with EFA < 0.20 CFU/mL/day (n = 187). The hazard ratio for 18-week mortality, comparing those with EFA < 0.20 to those with EFA > = 0.20, was 1.60 (95% confidence interval, 1.25, 2.04; P = .002). The lowest EFA group had lower median CD4 T-cell counts ( P < .01) and lower proportion of patients with CSF pleocytosis ( P < .001). Conclusions: EFA is associated with all-cause mortality in cryptococcal meningitis. An EFA threshold of > = 0.20 log10 CFU/mL/day was associated with similar 18-week mortality (37%) compared to 50% mortality with EFA < 0.20. This EFA threshold may be considered a target for a surrogate endpoint. This builds upon existing studies to validate EFA as a surrogate endpoint. Abstract : In cryptococcal meningitis trials, early fungicidal activity (EFA) reflecting Cryptococcus cerebrospinal fluid (CSF) clearance is used as a surrogate endpoint. We examined the relationship between EFA and survival in 738 Africans receiving amphotericin-based therapy: EFA < 0.20 log10 CFU/mL/day has decreased 18-week survival.